Genetic factors affecting food‐plant specialization of an oligophagous seed predator. (3rd December 2012) - Laukkanen, L.; Leimu, R.; Muola, A.; Lilley, M.; Mutikainen, P.
Abstract Several ecological and genetic factors affect the diet specialization of insect herbivores. The evolution of specialization may be constrained by lack of genetic variation in herbivore performance on different food‐plant species. By traditional view, trade‐offs, that is, negative genetic correlations between the performance of the herbivores on different food‐plant species favour the evolution of specialization. To investigate whether there is genetic variation or trade‐offs in herbivore performance between different food plants that may influence specialization of the oligophagous seed‐eating herbivore, Lygaeus equestris (Heteroptera), we conducted a feeding trial in laboratory using four food‐plant species. Although L. equestris is specialized on Vincetoxicum hirundinaria (Apocynaceae) to some degree, it occasionally feeds on alternative food‐plant species. We did not find significant negative genetic correlations between mortality, developmental time and adult biomass of L. equestris on the different food‐plant species. We found genetic variation in mortality and developmental time of L. equestris on some of the food plants, but not in adult biomass. Our results suggest that trade‐offs do not affect adaptation and specialization of L. equestris to current and novel food‐plant species, but the lack of genetic variation may restrict food‐plant utilization. As food‐plant specialization of herbivores may have wide‐ranging effects, for instance, on coevolving plant–herbivore interactions and speciation, it is essential to thoroughly understand the factors behind the specialization process. Our findings provide valuable information about the role of genetic factors in food‐plant specialization of this oligophagous herbivore.